Pengaruh Pengembangan Pariwisata Terhadap Perekonomian Lokal di Kawasan Wisata Pantai Senggigi, Lombok - Salihin Salihin (Lembaga Penelitian dan Pendidikan, 2025)
The development of tourism plays a vital role in supporting local economic growth, especially in coastal areas like Senggigi Beach, Lombok. This study aims to analyze the influence of tourism development on the local economy by examining employment rates, business activities, and income levels in the Senggigi area. Using a descriptive-quantitative approach, data were collected through surveys, interviews, and observation. The findings indicate that tourism development significantly contributes to increasing local income, employment opportunities, and small business growth. However, it also presents challenges such as environmental degradation and socio-cultural shifts. This study concludes that sustainable tourism planning is essential to maximize economic benefits while minimizing negative impacts. The results are expected to contribute to policymaking for regional development and sustainable tourism practices in coastal regions.